Capillary electrophoresis for monitoring bioprocesses. Issue 11 (8th May 2013) - Alhusban, Ala A.; Breadmore, Michael C.; Guijt, Rosanne M.
Abstract : Chemical characterization and monitoring of fermentation broths and cell culture media provide significant information on the changes occurring within these complex and dynamic systems. Analytical methods based on CE in capillaries and microchips are attractive for integration in instrumental tools to obtain this critical data, improving the understanding and control of bioprocesses. In this review, the use of CE for chemical characterization and monitoring fermentations is discussed, organized by analyte class, including organic acids, pharmaceuticals, proteins, sugars, amino acids, and metabolites published between 1992 and October 2012. A section is dedicated to the roles CE plays throughout the wine making process, where applications range from characterization and increase in fundamental understanding of the fermentation to forensic applications, verifying the authenticity of the wine.